2012
DOI: 10.4018/jghpc.2012010101
|View full text |Cite
|
Sign up to set email alerts
|

Technology Acceptance Model Applied to the Adoption of Grid and Cloud Technology

Abstract: Advances in grid technology in the past two decades have enabled some organizations to harness enormous computational power on demand. However, the prediction of widespread adoption of grid technology has not materialized, while cloud technology is increasingly gaining acceptance. Using the online survey engine - Survey Monkey, data were collected from individuals (242 respondents) in schools, businesses and government in USA to determine the influential factors in the adoption process of grid and cloud techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…Therefore, hypotheses H2 and H10 have been accepted and hypothesis H1 was rejected. This finding is in agreement with the argument presented by Udoh (2012) who found that trust explained 21% of variance in BI. Anxiety has been shown to have a significant negative effect on PEOU and PU; therefore, hypotheses H3 and H4 have been accepted.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, hypotheses H2 and H10 have been accepted and hypothesis H1 was rejected. This finding is in agreement with the argument presented by Udoh (2012) who found that trust explained 21% of variance in BI. Anxiety has been shown to have a significant negative effect on PEOU and PU; therefore, hypotheses H3 and H4 have been accepted.…”
Section: Discussionsupporting
confidence: 93%
“…In cloud computing environments, the effect of anxiety was also recognized in a recent study by Wu (2013), but this was included within the attitudes construct. Similarity, Udoh (2012) suggested that anxiety inhibits the adoption of cloud services and technologies, but anxiety was represented within antecedents of trust, as user apprehension about cloud security, privacy and reliability. In the current study, perceived risks and trust were considered as two different external variables that could affect PU and PEOU.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…It's also possible that a particular cloud provider will decide to disregard agreements, rules, or guarantees, or will otherwise falsify compliance, or will exploit the client organization in circumstances that aren't covered by the licensing agreement (Lansing and Sunyaev, 2016). Thus, the relationship between perceived trust in cloud service provider and individuals' attitude toward cloud technology adoption, have been shown to be significant and the key antecedent of behavioral intention to adopt the cloud (Udoh, 2012). Considering the above; the following hypothesis is formulated: H3: Trust in cloud service providers has a significant and positive influence on individuals' attitudes toward the cloud…”
Section: Hypotheses Development and Research Modelmentioning
confidence: 99%
“…Udoh, E. [5] pointed out that in recent years, the proportion of teachers and students in foreign language classrooms was unbalanced due to the continuous enrollment expansion of domestic universities. The original teaching methods and educational means were unable to satisfy the changing teaching needs, and the traditional foreign language teaching was in urgent need of reforming.…”
Section: Introductionmentioning
confidence: 99%